The Influence of Work Motivation and the Work Environment on Employee Performance in Faculty Agriculture University North Sumatra - Osman Manalu; Sutaryat Trisnamansyah; Husen Saeful Insan; Waska Warta (International Journal of Nusantara Islam, 2019)
This study aims to explain the effect of work motivation and work environment variables simultaneously and partially on Employee Performance at the Faculty of Agriculture, University of North Sumatra. The research method used quantitative models, using a questionnaire as a means of collecting data distributed to 50 employees at the Faculty of Agriculture, University of North Sumatra. The research method used is a quantitative method through an associative approach. Research location of the Faculty of Agriculture, University of North Sumatra. The sample selection method in this research is saturated sample (census). The data analysis technique used the classical assumption test, multiple linear regression test, f test and t test. The results of this study indicate: 1) Work motivation and work environment simultaneously influence employee performance. 2) Partially work motivation has a positive and significant effect on employee performance. 3) The work environment has a positive and significant effect on employee performance. The implication of this research is that observers of cleanliness and observers of work space so that the tasks given by employees are done well and it is hoped that with work motivation